Efficacy of cognitive bias modification interventions in anxiety and depression: Meta-analysis - Cristea, Ioana A.; Kok, Robin N.; Cuijpers, Pim (British journal of psychiatry, 2015)
Cognitive bias modification (CBM) interventions are strongly advocated in research and clinical practice. To examine the efficiency of CBM for clinically relevant outcomes, along with study quality, publication bias and potential moderators. We included randomised controlled trials (RCTs) of CBM interventions that reported clinically relevant outcomes assessed with standardised instruments. We identified 49 trials and grouped outcomes into anxiety and depression. Effect sizes were small considering all the samples, and mostly non-significant for patient samples. Effect sizes became non-significant when outliers were excluded and after adjustment for publication bias. The quality of the RCTs was suboptimal. CBM may have small effects on mental health problems, but it is also very well possible that there are no significant clinically relevant effects. Research in this field is hampered by small and low-quality trials, and by risk of publication bias. Many positive outcomes are driven by extreme outliers.